Mitochondrial genome of Tamarixia radiata (Hymenoptera: Chalcidoidea: Eulophidae) and phylogenetic analysis. Issue 2 (3rd July 2019) - Du, Yimin; Song, Xiang; Liu, Xinjun; Ouyang, Zhigang; Lu, Zhanjun
Abstract: Tamarixia radiata plays an important role in biological control of the psyllid Diaphorina citri Kuwayama, vector of the huanglongbing (HLB). In this study, we sequenced and analyzed the mitochondrial genome (mitogenome) of T. radiata, the first mitogenome of species in the family Eulophidae. This mitogenome was 14, 752 bp long and encoded 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs) and two ribosomal RNA unit genes (rRNAs). All 13 PCGs were initiated by the ATN (ATG, ATT, and ATA) codon. Twelve PCGs terminate with the stop codon TAA or TAG except for nad1 which end with the incomplete codon T−. Phylogenetic analysis showed that T. radiata got together with three Pteromalidae species, indicating the close relationship of Eulophidae and Pteromalidae.